2007
DOI: 10.1159/000098178
|View full text |Cite
|
Sign up to set email alerts
|

Inherited and Acquired Disorders of Platelet Function

Abstract: Platelet function defects are caused by rare congenital or, more frequently, by acquired disorders. They may lead to bleeding or thrombotic tendencies despite of normal platelet counts. The corresponding symptoms are often quite heterogeneous. A disorder of platelet function is suspected on the basis of case and family history, physical examination and platelet function tests. The so far primary screen of platelet dysfunctions, the bleeding time, is neither very sensitive nor specific and depends very much on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 123 publications
(100 reference statements)
0
15
0
1
Order By: Relevance
“…Since standard methods of platelet function analysis -like Born aggregometry and flow cytometry -are subjected to specialised laboratories, because of the complexity of the tests, perioperative platelet diagnostics is limited primarily to the platelet count, and the response to platelet transfusion is monitored by calculating the platelet-corrected count increment (CCI) and by the clinical parameter 'bleeding stopped' [27][28][29]. Experiences and studies of the last years have shown that POC-suitable coagulation and platelet function analyzers can be helpful in detection of perioperative platelet function disorders and for decisions in context with the therapy with PC, coagulation factor concentrates, and haemostatic drugs.…”
Section: Poc Platelet Function Testsmentioning
confidence: 99%
“…Since standard methods of platelet function analysis -like Born aggregometry and flow cytometry -are subjected to specialised laboratories, because of the complexity of the tests, perioperative platelet diagnostics is limited primarily to the platelet count, and the response to platelet transfusion is monitored by calculating the platelet-corrected count increment (CCI) and by the clinical parameter 'bleeding stopped' [27][28][29]. Experiences and studies of the last years have shown that POC-suitable coagulation and platelet function analyzers can be helpful in detection of perioperative platelet function disorders and for decisions in context with the therapy with PC, coagulation factor concentrates, and haemostatic drugs.…”
Section: Poc Platelet Function Testsmentioning
confidence: 99%
“…pregnancy, as well as deficiency of FXIII should be considered in differential diagnosis. Secondary functional platelet defects due to drugs or antiplatelet medication [65] or due to underlying disease, particularly myeloproliferative syndromes or liver and renal diseases [9], should be excluded.…”
Section: Rational Diagnostic Algorithm To Identify Platelet Dysfunctionsmentioning
confidence: 99%
“…The inherited platelet Gp defects constitute a group of very rare disorders of combined structural and functional platelet disturbances [1,[9][10][11]. The common denominator of these defects is an impaired platelet adhesion, activation and clot formation at sites of vascular injury.…”
Section: Introductionmentioning
confidence: 99%
“…In this first part of reviews on 'cellular haemostaseology, Kerstin Jurk and Beate Kehrel [1] provide an eminent exhaustive classification of inherited and acquired disorders of platelet function. Not only are the clinical features described in detail, but also the pathophysiology and the involved defect are clearly outlined, enabling the development of a systematic diagnostic schedule.…”
mentioning
confidence: 99%